Conflict Resolution Peace and Africa’s Quest for Development - Adefarasin, Victor (Indonesian Journal of Political Studies, 2023)
Africa is very rich both in human and natural resources. However, despite this, she is poor, undeveloped and impoverished as a result of crises, such as: political, religious, ethnic, cultural among others, which of course, affect her peace and quest for development. It is instructive and expedient to point it out that, no society can develop under strife, whatever may be the its source. A society that is conflict-ridden is not likely to get the peace that is predominantly necessary for development in all spheres of human activity. In order to achieve its intended objective, the paper discusses peace, conflict resolutions, meaning, features and dimensions of development. Also, some proposed recommendations are equally made. The paper concludes that, for Africa to develop, and join the comity of nations, there should be conflict resolutions and peace, this is because, peace is a necessary ingredient, sine qua non, hallmark and a great catalyst for true and all-round development.